Disruption of the vacuolar-type H+-ATPase complex in liver causes MTORC1-independent accumulation of autophagic vacuoles and lysosomes. Issue 4 (3rd April 2017) - Kissing, Sandra; Rudnik, Sönke; Damme, Markus; Lüllmann-Rauch, Renate; Ichihara, Atsuhiro; Kornak, Uwe; Eskelinen, Eeva-Liisa; Jabs, Sabrina; Heeren, Jörg; De Brabander, Jef K.; Haas, Albert; Saftig, Paul
ABSTRACT: The vacuolar-type H + -translocating ATPase (v-H + -ATPase) has been implicated in the amino acid-dependent activation of the mechanistic target of rapamycin complex 1 (MTORC1), an important regulator of macroautophagy. To reveal the mechanistic links between the v-H + -ATPase and MTORC1, we destablilized v-H + -ATPase complexes in mouse liver cells by induced deletion of the essential chaperone ATP6AP2. ATP6AP2-mutants are characterized by massive accumulation of endocytic and autophagic vacuoles in hepatocytes. This cellular phenotype was not caused by a block in endocytic maturation or an impaired acidification. However, the degradation of LC3-II in the knockout hepatocytes appeared to be reduced. When v-H + -ATPase levels were decreased, we observed lysosome association of MTOR and normal signaling of MTORC1 despite an increase in autophagic marker proteins. To better understand why MTORC1 can be active when v-H + -ATPase is depleted, the activation of MTORC1 was analyzed in ATP6AP2-deficient fibroblasts. In these cells, very little amino acid-elicited activation of MTORC1 was observed. In contrast, insulin did induce MTORC1 activation, which still required intracellular amino acid stores. These results suggest that in vivo the regulation of macroautophagy depends not only on v-H + -ATPase-mediated regulation of MTORC1.